Pelatihan Budidaya Sayuran Organik Kepada Biarawati Rumah Retret Dharmaningsih Desa Claket, Kecamatan Pacet, Mojokerto - Maniatul Fitan Kusuma; Ika Sari Tondang (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2023)
This training activity was carried out in order to increase the knowledge and skills of the common people, namely the Dharmaningsih Retreat House Nuns in Claket Village, Pacet District, regarding organic vegetables starting from upstream to downstream. The method used in this training activity is in the form of counseling or theoretical presentation, cultivation practice, making organic fertilizer, and evaluation with UPN Veterans East Java students. This activity was carried out for 2 days. The first day is for counseling and the second day is for making organic fertilizer, cultivation practices, and evaluation. The expected results from the implementation of this activity are increased ability and skills in cultivating organic vegetables and the implementation of plans to produce organic vegetables from private gardens in Batu City to be able to supply them to hospitals and churches.